Cytotoxic and antimicrobial potential of benzimidazole derivatives. Issue 8 (19th April 2021) - Küçükbay, Hasan; Uçkun, Mustafa; Apohan, Elif; Yeşilada, Özfer
Abstract: New benzimidazole derivatives were synthesized and their structures were characterized by spectroscopic and microanalysis techniques. The cytotoxic properties of ten benzimidazole derivatives, five of which were synthesized in our previous studies, were determined against the lung cancer cell line, A549, and the healthy lung epithelial cell line, BEAS‐2B. Among the ten compounds tested, based on the 72‐h incubation results, compound 12 was the most cytotoxic against the A549 cell line, whereas against the BEAS‐2B cell line, it was as cytotoxic as cisplatin. The IC50 values of compound 12 were 3.98 and 2.94 µg/ml for A549 and BEAS‐2B cells, respectively. The cisplatin values were 6.75 and 2.75 µg/ml for A549 and BEAS‐2B cells, respectively. Compounds 10, 8, 7, and 13 showed toxic effects against A549 cells, but were less toxic against BEAS‐2B cells than cisplatin. The antimicrobial activity of these compounds against pathogenic bacteria and yeasts was also evaluated based on their minimum inhibitory concentration (MIC) values. The compounds, except 12 and 13, generally showed higher antimicrobial activity against yeasts, compared with bacteria. Compound 12 showed better activity against Pseudomonas aeruginosa and Staphylococcus aureus than against Escherichia coli . Compounds 7, 8, and 11 were the most effective ones against the microorganisms, and yeasts were highly sensitive to these compounds with MIC values of 25–100 µg/ml. Abstract : The cytotoxic properties of ten benzimidazole derivatives, including five new ones, were determined against A549 lung cancer cells and BEAS‐2B healthy lung epithelial cells. Compound 12 was the most cytotoxic against the A549 cells, whereas it was as cytotoxic as cisplatin against the BEAS‐2B cells. All compounds, except 12 and 13, generally showed higher antimicrobial activity against yeasts, compared with bacteria.